Management of Madrasah Heads in Improving the Quality of Education - Jetry Urcy; Dina Ratna Sari (al-fikrah: Jurnal Manajemen Pendidikan, 2022)
This study aims to see how the implementation of madrasah principal management in improving the quality of education at MTsN 1 Batang Hari. The methodology used in this research is a qualitative method in the form of a case study. The respondent of this study was the head of madrasah and teachers at MTsN 1 Batang Hari. The research instruments are interviews, observation and documentation. Data analysis technique was used condensing or reducing data, presenting data and drawimg conclusion. The results of this study indicate that the implementation of madrasah principal management in improving the quality of education can be seen from the implementation of several programs. These programs start from planning management, implementation management and evaluation management. The planning program is comprehensive, integral, qualitative and quantitative, sustainable, efficient, realiable administration and resource accumulation. The implementation program includes teamwork, adequate facilities, information disclosure, involving stakeholders, students and parents in all activities. The evaluation program implement the principal’s managerial competencies, leadership abilities, skills in managing madrasahs, preserving the culture and climate of madrasahs and guiding educators and madrasahs employee.